Future data and security engineering : 5th International Conference, FDSE 2018, Ho Chi Minh City, Vietnam, November 28-30, 2018, Proceedings /: 5th International Conference, FDSE 2018, Ho Chi Minh City, Vietnam, November 28-30, 2018, Proceedings. (2018) - Unknown
No abstract available